Estimation of Social Costs of Highways in Japan - Fumitoshi Mizutani; Yusuke Suzuki; Shuji Uranishi (European Regional Science Association (ERSA), 2015)
The main purpose of this paper is to estimate and evaluate the social costs of highways in Japan. In general, with more people concerned about protecting the environment at both local and global levels, dependence on vehicular transportation in cities has brought about problems. Too much dependence on autos causes air pollution, which has detrimental health effects. Furthermore, traffic congestion wastes time, money, and energy. The most concerning issue related to continuing dependence on car use is global warming. In order to implement transport policies conducive to creating a sustainable environment, it is necessary to measure correctly the social costs of vehicular transport such as traffic accidents, air pollution, noise, global warming, and traffic congestion. By using a data set from Japan, this paper aims to estimate the social costs of vehicular transport on highways and to evaluate how extensive these social costs are by comparing, for example, highway fares relative to GDP. Our study has several distinguishing characteristics. The most important point is that we estimate each individual highwayfs social costs by considering average speed at the peak period, total traffic volume, types of vehicular transport and so on. Second, this study distinguishes five kinds of social costs of vehicular transport for individual highways in Japan: 1) traffic accidents, 2) air pollution, 3) noise, 4) global warming, and 5) traffic congestion. Third, by using a data set of over 50 individual highways in Japan in 2005, we analyze the relationship between the social costs of vehicular transport and traffic volumes in general. Last, by comparing highway fares, the degree of GDP, the fuel tax level, and other factors, we assess the magnitude of social costs, for the purpose of creating prudent transport policy. In order to attain the objectives mentioned above, we organize our study as follows. First, we summarize previous studies, with special attention to the kinds of social costs used, the kinds of sub-items considered in estimating social costs, the aggregate level, the method of estimation, and the magnitude of the social costs of vehicular transport. Second, we explain our method for estimating social costs. In this section, we describe specific equations for the five main categories of highwaysf social costs. Third, based on these equations, by using a data set for highways in Japan, we estimate the social costs of vehicular transport on highways. Last, by comparing highway fares, and GDP and so on, we evaluate how extensive highwaysf social costs actually are. In this section, we also summarize our major findings.
Keywords: R41; Q51; 330; Social Costs; Externalities; Highway; Transportation; Japan